The Impact of Business Mentoring on Micro, Small, Medium Enterprises Performance - Mohammad Adrian; Hendrati Dwi Mulyaningsih; Santi Rahmawati (Research Synergy Foundation, 2017)
This reasearch is conducted on MMSME (Micro Small Medium Enterprises) that are participated in the MMSME Syari’ah Mentoring Program by Academicians and Practitioners (PUSPA) organized by Bank Indonesia in Bandung. MMSME who participated in PUSPA program 2016 is MMSME that included in necessity entrepreneur where MMSME operated just to fullfil the life necessities. The purpose of this reasearch was to investigate the influence of the business mentoring on the MMSME performance in PUSPA program 2016. Researcher used quantitative research method. Data were analyzed using simple regression analysis and descriptive-causal analysis. The result showed that business mentoring affect the performance of MMSME that participated in PUSPA Program 2016. Based on the calculation, coefficient of determination (R2) can be seen the influence of business mentoring variable (X) on the performance (Y) is 74%. While the remaining 26% is influenced by other factors such as entrepreneurship competence and human resources.